Study of an arginine- and tryptophan-rich antimicrobial peptide in peri-implantitis - Zhang, Qian; Jiang, Yalei; He, Xiaotong; Liu, Liwei; Zhang, Xi (Frontiers in Bioengineering and Biotechnology, 2025)
The combination of hydrophilic arginine residues and hydrophobic tryptophan residues is considered to be the first choice for designing short-chain antimicrobial peptides (AMPs) due to their potent antibacterial activity. Based on this, we designed an arginine- and tryptophan-rich short peptide, VR-12. Peri-implantitis is a significant microbial inflammatory disorder characterized by the inflammation of the soft tissues surrounding an implant, which ultimately leads to the progressive resorption of the alveolar bone. This study found through antibacterial experiments, wound healing promotion experiments, and anti-inflammatory experiments that VR-12 inhibited and killed planktonic peri-implantitis-associated bacteria, inhibited biofilm formation, and disrupted mature biofilms. Additionally, VR-12 exhibited good biocompatibility with RAW264.7 cells and human gingival fibroblasts (HGFs) cells, promoting proliferation of both cell types. Moreover, VR-12 induced HGFs migration by promoting expression of migration-related factors, thereby promoting soft tissue healing. VR-12 also acted on lipopolysaccharide (LPS)-induced RAW264.7 cells, exerting excellent anti-inflammatory properties by affecting the secretion/expression of inflammation-related factors/genes. Therefore, VR-12 may be a good option for both warding off and treatmenting peri-implantitis.